Ethnic differences and inequities in paediatric healthcare utilisation in the UK: a scoping review - Zhang, CX; Quigley, MA; Bankhead, C; Bentley, T; Otasowie, C; Carson, C (BMJ Publishing Group, 2022)
Background Despite the increased policy attention on ethnic health inequities since the COVID-19 pandemic, research on ethnicity and healthcare utilisation in children has largely been overlooked.